2022
DOI: 10.3390/ijerph19148849
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Impacts of COVID-19 on Women and Men’s Psychological, Social, Vulnerable Work Situations, and Economic Well-Being

Abstract: The SARS-CoV-2 virus changed social reality worldwide, affecting people’s health and work life, particularly their anxiety levels. The purpose of this study is to verify the situation of women in terms of anxiety and social determinants in Spain during the pandemic. The sample consisted of 4686 people (3500 women and 1186 men). The tools used were the State-Trait Anxiety Inventory (STAI) and an ad hoc questionnaire to assess the work and mental situation of the participants. The results indicate a higher rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…16 This study also found that the total stigma was higher in male participants (41.84%) than in females (34.82%). This finding rebutted the previous study 10,11 that examined the gender disparities in reaction to the COVID-19 pandemic and showed that women in China and Spain experienced more psychological distress than men during the pandemic. This might relate to the difference in this study setting and the Arab culture and background of the participants.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…16 This study also found that the total stigma was higher in male participants (41.84%) than in females (34.82%). This finding rebutted the previous study 10,11 that examined the gender disparities in reaction to the COVID-19 pandemic and showed that women in China and Spain experienced more psychological distress than men during the pandemic. This might relate to the difference in this study setting and the Arab culture and background of the participants.…”
Section: Discussionsupporting
confidence: 70%
“…10 The proportion of women over males was more significant in the areas where the health crisis has had a more noticeable and impactful presence, with implications for the general population, especially women's physical, mental, and social health. 11 Although many studies have reported psychological (anxiety, depression, stress/ distress/ fear) impacts of COVID-19 from around the globe, only scanty studies reported the social stigma among COVID-19 patients and their experiences or coping/ societal re-integration strategies, including Arabian countries. Fortunately, few reports addressed the social stigma prevalent among healthcare workers worldwide, including Saudi Arabia, but none discussed the coping strategies and preferences of support.…”
Section: Introductionmentioning
confidence: 99%
“…More in detail, women experienced a higher increase in mental health disorders during the COVID-19 pandemic, when compared to men, probably because women were more likely to be affected by the social and economic consequences of the pandemic [7]. For example, at the global level, it emerged that the increase in the prevalence of major depressive disorder and anxiety disorders among women was greater than in men, with 35.5 million additional cases in women versus 17.7 million additional cases in men for major depressive disorder and 51.8 million additional cases in women versus 24.4 million additional cases in men for anxiety disorders.…”
Section: Introductionmentioning
confidence: 98%
“…[ 50 ]. In addition, compared to adult men, adult women are more likely to experience anxiety during the COVID-19 pandemic [ 79 ]. Isolation during the COVID-19 pandemic may also lead to unhealthy eating habits, such as overeating and snacking, which may lead to weight gain and nutritional imbalances that impair immune function [ 38 ].…”
Section: Resultsmentioning
confidence: 99%